2012
DOI: 10.2351/1.3695174
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond laser welded nanostructures and plasmonic devices

Abstract: Nanojoining, a burgeoning research area, becomes a key manufacturing of complicated nanodevices with functional prefabricated components. In this work, various nanojoining methods are first reviewed. For nanojoining of Ag/Au nanoparticles, three methods are investigated comparatively. Thermal annealing shows a two-step solid state diffusion mechanism. Laser annealing by millisecond pulses displays the thermal activated solid state diffusion. Meanwhile, two effects have been identified in femtosecond laser irra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(55 citation statements)
references
References 42 publications
1
53
0
1
Order By: Relevance
“…To date, most studies in this field using fs laser radiation to tailor nanomaterials have focused on the modification of bulk materials by introducing periodic surface structures [24,25]. Few studies have investigated the construction of nanostructures from combinations of nanowires and nanoparticles, as published work has centered on the optimization of joining processes to get bonded structures via plasmonic heating [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…To date, most studies in this field using fs laser radiation to tailor nanomaterials have focused on the modification of bulk materials by introducing periodic surface structures [24,25]. Few studies have investigated the construction of nanostructures from combinations of nanowires and nanoparticles, as published work has centered on the optimization of joining processes to get bonded structures via plasmonic heating [26,27].…”
Section: Introductionmentioning
confidence: 99%
“…A first study has been conducted by Stengl [111], where they synthesized mesoporous TiO 2 -graphene oxide nanocomposites with a specific surface area of almost ∼80-200 m 2 g −1 , larger than those of TiO 2 nanoparticles (P25) [108].The authors reported a better photocatalytic degradation of butane in the gas phase attributed different effects including the increase in specific surface area. By developing suitable nano-manipulation and nano-assembling techniques [112] porous graphene is a very attractive materials for a range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…From then on, femtosecond laser was gradually noticed as a powerful tool in micromachining due to its excellent performance in high machining quality and precision [2], especially in solid materials ablation, i.e., ablate 2D structures on metals [3][4][5], polymers [6,7], and crystals [8,9]. Meanwhile, 2D photonic devices manufacturing [10,11], surface engineering [12][13][14][15] and the formation of novel polyynes, 1D molecular carbon wire [16], nanojoining [17,18], and casting [19] based on femtosecond laser irradiation are also well developed and attracted many scientific interests. Apart from the aforementioned 2D manufacturing applications of which functional features are fabricated either directly on the surface of the materials, or fabricated according to in-plane machining pattern, femtosecond laser micromachining is unique in its 3D micro-/nanostructuring ability attributing to the nonlinear nature of the multiphoton absorption [20][21][22]: (1) The structure changes can be confined to the focal volume as the intensity distribution for multiphoton absorption is spatially narrower than linear absorption, providing an ideal tool for 3D manufacturing with high spatial resolution; (2) the absorption of laser energy is independent with materials, ensuring its wide applications in various materials; and (3) no thermal effect occurs during femtosecond laser irradiation since the lattice heating time (*10 ps) is much longer than the pulse duration of femtosecond laser (\1 ps), and thus femtosecond laser machining is more precise than the fabrication with the lasers with longer pulse durations.…”
Section: Introduction Of Femtosecond Laser Threedimensional Internal mentioning
confidence: 99%